Gallstones after bariatric surgery: mechanisms and prophylaxis - Chen, Shenhao; Zheng, Yamin; Cai, Jie; Wu, Yuzhao; Chen, Xi (Frontiers in Surgery, 2025)
Gallstones represent a common yet often underappreciated complication following bariatric surgery, with reported incidence rates ranging widely from 10.4% to 52.8% within the first postoperative year. Multiple factors contribute to gallstone formation in this setting, including intraoperative injury to the hepatic branch of the vagus nerve, alterations in bile composition, reduced food intake, shifts in gastrointestinal hormone levels, and dysbiosis of the gut microbiota. Notably, the risk of cholelithiasis varies by surgical procedure, with sleeve gastrectomy (SG) generally associated with a lower incidence compared to Roux-en-Y gastric bypass (RYGB). Prophylactic cholecystectomy during bariatric surgery may benefit patients with preexisting gallstones, whereas preserving the hepatic branch of the vagus is an important technical consideration, particularly in RYGB, to mitigate postoperative gallstone risk. Pharmacological interventions, such as ursodeoxycholic acid (UDCA), have demonstrated efficacy in preventing gallstones and reducing subsequent cholecystectomy rates. However, consensus is lacking on the optimal dosing, duration, and administration frequency of UDCA across different bariatric procedures. Additionally, dietary measures, such as moderate fat intake or fish oil supplementation, have shown promise in alleviating lithogenic processes. Emerging evidence supports the use of probiotics as a safe and patient-friendly adjunct or alternative to UDCA, given their ability to improve gut dysbiosis and reduce gallstone formation. Further high-quality studies are needed to define standardized prophylactic strategies that balance efficacy with patient adherence, offering personalized gallstone prevention protocols in the era of widespread bariatric surgery.